Toxicological study of chromium and its interaction with GA3 on germination of different cultivars of paddy (Oryza sativa L.) - Gyawali, Rajendra; Lekhak, H. D. (Ecoprint: An International Journal of Ecology, 2010)
The study was carried out to find the toxic effect of chromium and the role of GA3 to overcome the toxic effect imposed by chromium on five different cultivars of paddy (Oryza sativa L.) viz. cv Pokhareli Masino, cv Khunul-2, cv Jorpati Local, cv Khumal-6 and cv Taichung Local from Kathmandu valley. Germination experiments were carried out in petri dishes for seven days at 26±2°C temperature and potassium dichromate (K2Cr2O7) was used as a source of chromium. The degree of inhibition in germination was variable with type of the cultivars and range of chromium concentration. Increase in concentration let to inhibition in germination. tolerace of the five different cultivars of paddy was: Taichung Local < Khumal-6 < Mansuli Local < Khumal-2 < Pokhareli Masino. The value of effective concentration (EC50) that inhibited the 50 percent germination was found at 287.5, 177.5, 147.5, 87.5 and 32.5 ppm for Pokhareli Masino, Khumal-2, Mansuli Local, Khumal-6 and Taichung Local, respectively. Exogenously applied plant hormone GA3 in combination with crhomium was found partly able to overcome the chromium toxicity but was unable to fully suppress the toxicity imposed by chromium on seed germination of paddy. Key words: Paddy; Germination; Chromium; EC50; GA3; Toxicity doi: 10.3126/eco.v12i0.3194 Ecoprint: An International Journal of Ecology 12: 27-33, 2005